Pengaruh Customer Experience, E-Wom, Dan Service Recovery Terhadap Loyalitas Pelanggan Chobite Kabupaten Sidoarjo - Sofia Nur Ajizah; Ida Ayu Sri Brahmayanti (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effect of customer experience, electronic word of mouth (e-WOM), and service recovery on customer loyalty at Chobite Sidoarjo. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to customers of Chobite Sidoarjo. The sampling technique used was purposive sampling, while data analysis was conducted using SPSS, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that customer experience, e-WOM, and service recovery simultaneously have a positive and significant effect on customer loyalty. Partially, each independent variable also shows a significant influence on customer loyalty. These findings suggest that positive customer experiences, digital consumer communication, and effective service recovery practices play an important role in building and maintaining customer loyalty.